Epidemiology of Transient Ischemic Attacks Using Time- or Tissue-Based Definitions: A Population-Based Study. Issue 3 (March 2017) - Degan, Diana; Ornello, Raffaele; Tiseo, Cindy; De Santis, Federica; Pistoia, Francesca; Carolei, Antonio; Sacco, Simona
Abstract : Background and Purpose—: Transient ischemic attack (TIA) epidemiology may have changed in recent years as a consequence of improved identification and treatment of vascular risk factors. Our aim was to provide updated information about TIA epidemiology in Italy. Methods—: Cases of first-ever TIA were ascertained from January 1, 2011, until December 31, 2012, in a population-based prospective registry. All residents in the L'Aquila district with an incident TIA were included and followed up to 2 years after the event. Outcome events were recurrent TIA, nonfatal and fatal stroke, nonfatal and fatal myocardial infarction, and all-cause mortality. Results—: A total of 210 patients with a TIA according to the traditional time-based definition were included (51.4% women); 151 patients (71.9%) with transient symptoms and negative brain neuroimaging were broadly considered as tissue-based TIA, 29 patients (13.8%) had transient symptoms and evidence of a congruous acute ischemic lesion, and 30 patients (14.3%) had an acute neurovascular syndrome. The crude annual incidence rate for traditional time-based TIA was 35.2 per 100 000 (95% confidence interval, 30.6–40.3) and 28.6 per 100 000 (95% confidence interval, 24.1–33.5) when standardized to the 2011 European population. The incidence peaked in subjects aged ≥85 years, in both sexes. At 2 years, outcome events occurred in 50 patients (23.8%) including 15 patients (7.1%) with nonfatal or fatal strokes. Conclusions—: Our population-based study found a low annual TIA incidence rate and a fair TIA prognosis confirming the effectiveness of preventive strategies for cardiovascular diseases. We also proved the nonfitting applicability of the tissue-based definition in our district. Abstract : Supplemental Digital Content is available in the text.